Recent Progress in the Pathophysiology and Treatment of FSGS Recurrence. Issue 2 (11th January 2013) - Cravedi, P.; Kopp, J. B.; Remuzzi, G.
<x xml:space="preserve">Abstract</x> Focal segmental glomerulosclerosis (FSGS) is a glomerular disease characterized by proteinuria, frequent progression to end‐stage renal disease, and recurrence after kidney transplantation in ∼25% of patients, which negatively impacts long‐term allograft survival. Experimental studies suggest that abnormalities in T and, possibly, B cells may represent one initial pathogenic trigger, leading to podocyte injury and progressive loss. New data also support the existence of circulating permeability factors able to damage the podocytes, but no single molecule has been consistently identified as the causal pathogenic element in FSGS recurrence. Unfortunately, major progress from mechanistic studies has not translated into substantial advancements in patient treatment, with plasmapheresis (PP) and high doses of cyclosporine (CsA) remaining the mainstays of therapy. Despite consistent experimental and clinical evidence that treatment of proteinuria slows renal function decline in proteinuric nephropathies, maximal use of antiproteinuric agents such as renin angiotensin system antagonists is not routine in the management of FSGS recurrence. More recently, encouraging results have been reported with anti‐CD20 depleting antibody rituximab, but further studies are needed to establish its safety/efficacy profile.